Are diatoms ″green″ aluminosilicate synthesis microreactors for future catalyst production? - Koehler, Lydia; Machill, Susanne; Werner, Anja; Selzer, Carolin; Kaskel, Stefan; Brunner, Eike (Molecules, 2017)
Diatom biosilica may offer an interesting perspective in the search for sustainable solutions meeting the high demand for heterogeneous catalysts. Diatomaceous earth (diatomite), i.e., fossilized diatoms, is already used as adsorbent and carrier material. While diatomite is abundant and inexpensive, freshly harvested and cleaned diatom cell walls have other advantages, with respect to purity and uniformity. The present paper demonstrates an approach to modify diatoms both in vivo and in vitro to produce a porous aluminosilicate that is serving as a potential source for sustainable catalyst production. The obtained material was characterized at various processing stages with respect to morphology, elemental composition, surface area, and acidity. The cell walls appeared normal without morphological changes, while their aluminum content was raised from the molar ratio n(Al):n(Si) 1:600 up to 1:50. A specific surface area of 55 m2/g was measured. The acidity of the material increased from 149 to 320 μmol NH3/g by ion exchange, as determined by NH3 TPD. Finally, the biosilica was examined by an acid catalyzed test reaction, the alkylation of benzene. While the cleaned cell walls did not catalyze the reaction at all, and the ion exchanged material was catalytically active. This demonstrates that modified biosilica does indeed has potential as a basis for future catalytically active materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Aluminosilicate; Biosilica; Catalysis; Diatoms